Strategy for Improving the Quality of Public Services at PDAM Company Tirta Mangakaluku Palopo City - Syahruddin Syah; Jusmia Paseba (Universitas Negeri Makassar, 2020)
This research is motivated by a problem in which the Regional Water Company Tirta Mangkaluku Palopo City has received many complaints from customers in providing services starting from water rates, water quality that is still cloudy, abnormal water discharge and water that does not flow at all. In general, this study aims to determine how the strategy of the Tirta Mangkaluku Regional Drinking Water Company in improv the quality of public services. Palopo. This research uses descriptive qualitative research type. The focus of this research is on the service strategy of PDAM TM Palopo City. Data collection techniques are interviews, observations, and also based on documents from the Regional Water Company Tirta Mangkaluku Palopo City. The results showed that the strategy for improving the quality of public services at the Tirta Mangkaluku Regional Drinking Water Company in Palopo City on the core strategy, consequences, customers and control was adequate in realizing public services but the cultural strategy had not provided the quality of public services in accordance with the expectations of stakeholders, because the community still continues to complain about the attitudes, behavior and services provided to the community as customers.